Mineralogical and Edaphological Characterization of the Soils of Huimanguillo and Jalpa de Méndez, Tabasco - Flores Candelero, Genesis Haniel; Navarro Rangel, José Angel (JOURNAL OF BASIC SCIENCES, 2025)
This study addresses the mineralogical and edaphological characterization of soils from the municipalities of Huimanguillo and Jalpa de Méndez, in Tabasco, Mexico. Through X-ray diffraction (XRD) analysis and soil profile descriptions, variations were identified in mineral composition and cation exchange capacity (CEC) between the two sites. The soils from Jalpa de Méndez showed greater mineral diversity, while those from Huimanguillo presented signs of alteration due to anthropogenic activity. Physical properties such as texture, color, and moisture, along with biological activity and organic matter content, also varied among the analyzed profiles. The results provide valuable information for understanding the productive potential of these soils and for developing appropriate strategies for their conservation and sustainable management.